2021
DOI: 10.4149/bll_2021_023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, maternal and neonatal outcomes of pregnant women with SARS-CoV-2 infection in Turkey

Abstract: OBJECTIVES: To evaluate clinical features, laboratory test results, maternal and neonatal outcomes of pregnant patients with the Coronavirus disease (COVID-19). BACKGROUND: COVID-19 is a highly contagious disease caused by a severe acute respiratory coronavirus 2 (SARS-CoV-2). Healthy pregnant women are more susceptible to developing COVID-19. METHODS: We reviewed clinical data from pregnant patients with a laboratory-confi rmed SARS-CoV-2, who were admitted to two tertiary care hospitals in Turkey. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
8
0
4
Order By: Relevance
“…12 In another study from Turkey, 75% of pregnant women participants were symptomatic and similar to the symptom ranking in our results, they also found that cough (62.5%) and fever (54.1%) were the most common symptoms during COVID-19 infection. 13 The results of this study showed that the rate of premature birth in pregnant women with confirmed COVID-19 was 10%. Similarly, in a study conducted with the early data in China, the premature birth rate was found to be 12.1%, and in the same study, PCR positivity in newborns was reported as 9%, similar to our results.…”
Section: Discussionmentioning
confidence: 65%
“…12 In another study from Turkey, 75% of pregnant women participants were symptomatic and similar to the symptom ranking in our results, they also found that cough (62.5%) and fever (54.1%) were the most common symptoms during COVID-19 infection. 13 The results of this study showed that the rate of premature birth in pregnant women with confirmed COVID-19 was 10%. Similarly, in a study conducted with the early data in China, the premature birth rate was found to be 12.1%, and in the same study, PCR positivity in newborns was reported as 9%, similar to our results.…”
Section: Discussionmentioning
confidence: 65%
“…[1] In the study of Özsürmeli et al conducted in our country, preeclampsia was found 8.3%. [22] At the time of publication of the study by fiahin et al, 34.5% of the pregnancies were terminated. Preeclampsia was detected in 1 (10%) of 10 pregnant women who gave birth.…”
Section: Discussionmentioning
confidence: 98%
“…Although a high number of COVID-19 during pregnancy were reported in Turkey, there are still few studies regarding maternal or perinatal outcomes of COVID-19 infection during pregnancy. [11,12] The study, including 533 patients, reported that most of the pregnant women diagnosed with COVID-19 had mild symptoms (95.5%), and only 0.5% of the cases had severe symptoms. [12] In our study, 40.4% of the patients diagnosed with COVID-19 suffered from severe symptoms.…”
Section: Discussionmentioning
confidence: 99%